Printable Bioelectronics To Investigate Functional Biological Interfaces. Issue 43 (30th September 2015) - Manoli, Kyriaki; Magliulo, Maria; Mulla, Mohammad Yusuf; Singh, Mandeep; Sabbatini, Luigia; Palazzo, Gerardo; Torsi, Luisa
Abstract: Thin‐film transistors can be used as high‐performance bioelectronic devices to accomplish tasks such as sensing or controlling the release of biological species as well as transducing the electrical activity of cells or even organs, such as the brain. Organic, graphene, or zinc oxide are used as convenient printable semiconducting layers and can lead to high‐performance low‐cost bioelectronic sensing devices that are potentially very useful for point‐of‐care applications. Among others, electrolyte‐gated transistors are of interest as they can be operated as capacitance‐modulated devices, because of the high capacitance of their charge double layers. Specifically, it is the capacitance of the biolayer, being lowest in a series of capacitors, which controls the output current of the device. Such an occurrence allows for extremely high sensitivity towards very weak interactions. All the aspects governing these processes are reviewed here. Abstract : Electrolyte‐gated thin‐film transistors with integrated protein recognition elements can be used to probe subtle changes occurring in a biolayer. Comparison of the biochemical processes occurring in solution and at the electrode is critical.